Kajian Pengaruh Rapat Arus pada Pelapisan Hard Chrome terhadap Kekerasan Permukaan Baja Karbon Rendah (ST 37) - Nurdin Nurdin; Ichsan Maulana; Yuniati Yuniati; Ismi Amalia (Politeknik Negeri Lhokseumawe, 2022)
AbstractThe hard chrome process is one of the most widely used metal finishing methods to avoid corrosion, besides that hard chrome can improve metal quality such as hardness. The Hard chrome process is carried out by varying the current density of 30 Amp/dm2, 30 Amp/dm2, 40 Amp /dm2 and 50 Amp/dm2 with a coating time of 40 minutes at a solution temperature of 50 ᵒC. After the hard chrome process, the surface hardness test was carried out using a microvickers indent with a loading of 25 g.f. The results showed that the layer thickness and hardness increased when the current strength increased. The highest hardness value occurred at a current of 4 amperes of 551.6 VHN and a layer thickness of 1.80 microns.